Repetitive Transcranial Magnetic Stimulation Enhances Recovery in Central Cord Syndrome Patients - Hana Choi; Kyung Cheon Seo; Tae Uk Kim; Seong Jae Lee; Jung Keun Hyun (Annals of Rehabilitation Medicine, 2019)
Objective To investigate the effect of repetitive transcranial magnetic stimulation (rTMS) on neurological and functional recovery in patients with central cord syndrome (CCS) involving the upper extremities between the treated and non-treated sides of the treated group and whether the outcomes are comparable to that of the untreated control group. Methods Nineteen CCS patients were treated with high-frequency (20 Hz) rTMS over the motor cortex for 5 days. The stimulation side was randomly selected, and all the subjects received conventional occupational therapy during the rTMS-treatment period. Twenty CCS patients who did not receive rTMS were considered as controls. Clinical assessments, including those by the International Standard for Neurological Classification of Spinal Cord Injury, the Jebsen-Taylor Hand Function Test, and the O'Connor Finger Dexterity Test were performed initially and followed up for 1 month after rTMS treatment or 5 weeks after initial assessments. Results The motor scores for upper extremities were increased and the number of improved cases was greater for the treated side in rTMS-treated patients than for the non-treated side in rTMS-treated patients or controls. The improved cases for writing time and score measured on the Jebsen-Taylor Hand Function Test were also significantly greater in number on the rTMS-treated side compared with the non-treated side and controls. There were no adverse effects during rTMS therapy or the follow-up period. Conclusion The results of the application of high-frequency rTMS treatment to CCS patients suggest that rTMS can enhance the motor recovery and functional fine motor task performance of the upper extremities in such individuals.